2021
DOI: 10.3892/ol.2021.13177
|View full text |Cite
|
Sign up to set email alerts
|

Effects of trans‑(±)‑kusunokinin on chemosensitive and chemoresistant ovarian cancer cells

Abstract: Ovarian cancer ranks eighth in cancer incidence and mortality among women worldwide. Cisplatin-based chemotherapy is commonly used for patients with ovarian cancer. However, the clinical efficacy of cisplatin is limited due to the occurrence of adverse side effects and development of cancer chemoresistance during treatment. Trans-(±)-kusunokinin has been previously reported to inhibit cell proliferation and induce cell apoptosis in various cancer cell types, including breast, colon and cholangiocarcinoma. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 76 publications
(114 reference statements)
1
4
0
Order By: Relevance
“…In this study, ( )KU had IC 50 values on ovarian cancer (A2780, SKOV3 and OVCAR3) that were similar to CIS (chemotherapeutic drug for ovarian cancer treatment) and our previous report [ 10 ]. ( )KU showed strong cytotoxicity against breast cancer cell lines on both minimally potential migration (MCF7) and aggressive migration (BT549 and Hs578T).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…In this study, ( )KU had IC 50 values on ovarian cancer (A2780, SKOV3 and OVCAR3) that were similar to CIS (chemotherapeutic drug for ovarian cancer treatment) and our previous report [ 10 ]. ( )KU showed strong cytotoxicity against breast cancer cell lines on both minimally potential migration (MCF7) and aggressive migration (BT549 and Hs578T).…”
Section: Discussionsupporting
confidence: 83%
“…Previously, we reported that kusunokinin had a cytotoxic effect on cancer cell lines, for instance, ovarian cancer (A2780, A2780cis, SKOV3 and OVCAR3), colon cancer (HT-29), cholangiocarcinoma (KKU-M213 and KKU-K100) and several breast cancer subtypes, including luminal A (MCF7), basal-A (MDA-MB-468) and basal-B (MDA-MB-231) [ 9 , 10 ]. The natural ( )KU showed significantly increased apoptosis on MCF7 and MDA-MB-468 cells after treatment for 24 h. ( )KU decreased anti-apoptotic protein (bcl2) and increased apoptotic protein (bax, cytochrome c, caspase-7 cleaved and caspase-8 cleaved) on MCF-7 cells at 72 h [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study, we reported that natural (−)-kusunokinin showed anticancer activity against breast, colon and lung cancer [ 19 , 21 ]. In addition, the synthetic (±)-kusunokinin racemic-compounds also exhibited cytotoxic activity in many cancer cells including breast, cholangiocarcinoma, colon, and ovarian cancer cells [ 20 , 24 ]. In this present study, we aimed to evaluate the cytotoxicity of (±)-kusunokinin derivatives ((±)-TTPG-A and (±)-TTPG-B) in aggressive cancer-cells.…”
Section: Discussionmentioning
confidence: 99%